2016
DOI: 10.1115/1.4032655
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Modeling of Extreme Heat Flux Microchannel Coolers for GaN-on-SiC Semiconductor Devices

Abstract: Gallium nitride (GaN) high-electron-mobility transistors (HEMTs) dissipate high power densities which generate hotspots and cause thermomechanical problems. Here, we propose and simulate GaN-based HEMT technologies that can remove power densities exceeding 30 kW/cm 2 at relatively low mass flow rate and pressure drop. Thermal performance of the microcooler module is investigated by modeling both single-and two-phase flow conditions. A reduced-order modeling approach, based on an extensive literature review, is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Zhang et al (2016g) observed that at low inlet subcooling temperatures of 10 and 40 K, the heat transfer coefficient was significantly increased with a reduced pressure drop along the channel. Lee et al (2016) computed the heat transfer coefficient of GaN-on-SiC semiconductors devices for the various flow regimes. For the bubbly flow regime, an increase in mass flux suppressed nucleate boiling growth, which consequentially decreased the heat transfer coefficient.…”
Section: Numerical Modelling Of the Heat Transfer Coefficientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al (2016g) observed that at low inlet subcooling temperatures of 10 and 40 K, the heat transfer coefficient was significantly increased with a reduced pressure drop along the channel. Lee et al (2016) computed the heat transfer coefficient of GaN-on-SiC semiconductors devices for the various flow regimes. For the bubbly flow regime, an increase in mass flux suppressed nucleate boiling growth, which consequentially decreased the heat transfer coefficient.…”
Section: Numerical Modelling Of the Heat Transfer Coefficientsmentioning
confidence: 99%
“…They discovered that the pressure drop increased significantly with an increase in inlet velocity. Lee et al (2016) studied GaN-on-SiC semiconductor microchannel coolers devices with high heat flux, focusing on the heat transfer and flow phenomena. They compared the effect of tapered channel design (45 • tapered) with an un-tapered channel design at varying mass fluxes.…”
Section: Numerical Modelling Of the Pressure Dropmentioning
confidence: 99%
“…Recent progress in GaN-based high-electron mobility transistors (HEMTs) has confirmed them to be the main transistor technology for upcoming high-power devices at high-frequency operation because of their excellent electronic properties, especially high-electron saturation velocity, and high breakdown voltage [1][2][3][4][5][6]. Multifinger devices with a compact layout are required for high-power operation.…”
Section: Introductionmentioning
confidence: 99%
“…However, GaN HEMTs dissipate large heat fluxes which create hotspots that can cause significant degradation in performance [3] when maximum operating temperatures of ~250 o C are exceeded. To alleviate the problem of hotspots, silicon carbide (SiC) heat spreaders have been used due to their high thermal conductivity of 370 W/m.K at 20 o C [4]. However, since the thermal conductivity of SiC decreases significantly as temperature increases [5], the use of SiC alone is not practical for hot spot mitigation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Calame et al [10] used experiments and numerical simulations to study the dissipation of 4 kW/cm 2 over a 1.2 × 5 mm 2 active area of a GaN on SiC semiconductor using water-cooled microchannel coolers, while the experimental study of Lee et al [11] investigated how to dissipate a heat flux of 11.9 kW/cm 2 over eight heat sources of size 350 × 150 µm 2 on a 7 × 7 mm 2 silicon (Si) die with a maximum hotspot temperature of 175°C. Recently, Lee et al [12,13] used 3-D numerical simulations to analyse the thermal conditions when a total power of 92.4 W is applied to 40 multiple gates (a heat flux of 330 kW/cm 2 is applied to each gate) located on GaN HEMTs on a SiC-based microchannel heat sink using water and methanol as a coolants in single and two phase flow conditions. Other relevant studies have focused on the effect of using very high thermal conductivity substrates to enhance heat spreading for GaN and a number of these have analysed diamond heat spreaders [14 -16] since diamond's thermal conductivity is 2200 W/m.K -5.5 times greater than copper [17].…”
Section: Introductionmentioning
confidence: 99%